Early warning systems for malaria outbreaks in Thailand: an anomaly detection approach - Srimokla, O; Pan-ngum, W; Khamsiriwatchara, A; Padungtod, C; Tipmontree, R; Choosri, N; Saralamba, S (BioMed Central, 2024)
Background: Malaria continues to pose a significant health threat. Rapid identification of malaria infections and the deployment of active surveillance tools are crucial for achieving malaria elimination in regions where malaria is endemic, such as certain areas of Thailand. In this study, an anomaly detection system is introduced as an early warning mechanism for potential malaria outbreaks in countries like Thailand.